Semi-Automated PCR Method for Quantitating MDR1 Expression - S. Zhao; U. Consoli; R. Arceci; J. Pfeifer; W.S. Dalton; M. Andreeff (BioTechniques)
The MDR1 gene is involved in drug resistance in many hematopoietic and solid tumors. The Quantitative PCR System 5000TM (QPCR-5000; Perkin-Elmer) is a new instrument system that uses electrochemiluminescence to automatically quantitate polymerase chain reaction (PCR) products. A comparative study between radioactively labeled PCR (32P-PCR) and QPCR was performed to analyze the MDR1 gene expression in the drug-resistant (Doxorubicin) cell lines Dox40, Dox6, the parental cell line 8226/S, CEM Dox1 and three acute myeloid leukemia (AML) patient samples. Using the Dox40 and Dox6 resistant cell lines, we compared the sensitivities of QPCR and 32P-PCR. A strong signal was obtained from QPCR at 20 to 25 cycles (which is in the linear range for quantitation), while a weak signal was obtained using 32P-PCR at the same cycle number. Dilution experiments gave better precision with the QPCR than with the radioactive method. AML samples were studied with the MDR1-specific MAbs MRK16 and 4E3, and the efflux function was analyzed using Rh-123 retention in the absence or presence of verapamil. The three samples showed high (D = 0.79), medium (D = 0.52) and negative (D = 0.08) p-glycoprotein (P-gp) levels and correlated with efflux function. The MDR1/β2-M mRNA ratios for 32P-PCR were 0.41, 0.40 and 0.12, respectively, and were 0.127, 0.097 and 0.028, respectively, for QPCR. There were significant differences between the samples with high and medium P-gp levels comparing the two methods. Very low levels of MDR1 in CEM Dox1 cells could be detected only by QPCR. In conclusion, QPCR was found to be more reproducible, accurate and sensitive than 32P-PCR.